The Digital Economy is the ‘New Normal’ - de Percy, Michael (Journal of Telecommunications and the Digital Economy, 2025)
This editorial introduces a new issue of the Journal of Telecommunications and the Digital Economy, exploring the growth of the digital economy post-COVID-19. The pandemic accelerated online interactions, revealing a lag in social norms despite decades-old technologies. Developed nations integrate AI into shopping, while developing countries advance rapidly, yet design principles remain rooted in tradition. The contributions in this issue underscore the human element in technology adoption and the Journal’s role in bridging telecommunications’ legacy with today’s digital challenges, enriching understanding of the evolving digital economy.